2023
DOI: 10.3389/fpsyt.2022.1070681
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth of people who have experienced earthquakes: Qualitative research systematic literature review

Abstract: IntroductionEarthquakes can have a variety of physical, emotional, and social effects on the people who experience them. Post-traumatic Growth (PTG) results from people attempting to reconstruct their lives after experiencing a traumatic event. We intend to inform the local community of the importance of disaster psychology by identifying and analyzing the literature on post-traumatic growth experiences of subjects who experienced earthquakes.MethodsThis study applied a systematic review of qualitative researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Traditionally, rumination has been associated with adverse outcomes, such as depression and anxiety (18). In recent years, most researchers have also uncovered a different perspective: the process of rumination, wherein individuals reflect on the impact and significance of a profoundly traumatic event, can lead to newfound wisdom and personal growth (19,20). The majority of previous studies have demonstrated the influence of rumination on personal growth, with the nature of its effects being contingent upon factors such as the time elapsed since the events and the particular subcomponents of rumination (21)(22)(23).…”
Section: Trait Rumination and Post-stress Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, rumination has been associated with adverse outcomes, such as depression and anxiety (18). In recent years, most researchers have also uncovered a different perspective: the process of rumination, wherein individuals reflect on the impact and significance of a profoundly traumatic event, can lead to newfound wisdom and personal growth (19,20). The majority of previous studies have demonstrated the influence of rumination on personal growth, with the nature of its effects being contingent upon factors such as the time elapsed since the events and the particular subcomponents of rumination (21)(22)(23).…”
Section: Trait Rumination and Post-stress Growthmentioning
confidence: 99%
“…To explore the occurrence of significant events, we employed the Adolescent Self-Rating Life Events Checklist (49) to evaluate the influence of adverse life events on Chinese college students over the preceding 12 months. This checklist comprises 27 items (e.g., "Relatives and friends suffer from acute or serious illness" and "Being discriminated against") and encompasses six key dimensions: interpersonal relationship (1, 2, 4, 15, 25), learning pressure (3,9,16,18,22), punishment (17,18,19,20,21,23,24), loss (12,13,14), health adaptation (5,8,11,27), and other (6,7,23,24). Each item was assessed with a 5-point Likert scale to rate the influence of negative life events on Chinese college students: no influence (1), mild influence (2), moderate influence (3), severe influence (4), and extremely severe influence (5).…”
Section: Research Instruments Adolescent Self-rating Life Events Chec...mentioning
confidence: 99%